Facile, sustainable and unassisted plain water oxidation on Au/Ce0.9Ti0.1O2 nanorods in direct sunlight - Dubey, Anjani; Mishra, Abhaya Kumar; Negi, Sanjay Singh; Gopinath, Chinnakonda S. (Journal of Chemical Sciences, 2022)
Impressive rate of solar water oxidation to molecular oxygen (O-2) has been demonstrated on nanorods (NRs) of Ce0.9Ti0.1O2 (CT-NR) and Au-deposited CT-NR (Au-CT-NR) photocatalysts with a sacrificial agent (Fe3+) and in plain water in one sun condition, direct sunlight and with lambda >= 455 nm. Probably the highest 0 2 yield of 11 mmol/h.g was observed with Au-CT-NR thin film in plain water in direct sunlight, with no sacrificial agent or applied potential. Photoelectrochemical measurements demonstrate a marked reduction in oxidation onset potential of Au-CT-NR by 150 mV with stable photocurrent (0.75 mA/cm(2)), compared to CT-NR (0.23 mA/cm(2)), indicating the operative of plasmon-induced resonant energy transfer (PIRET) process. Effective electron quenching by nanogold and hence low recombination in the depletion region is a critical step for the observation of a high rate of oxygen evolution. In addition to this, a predominant change in the nature of the valence band from O-2p dominated on CeO2 to Ce-4f dominated with CT-NR (due to Ti4+ introduction in CeO2), the efficient light absorption of photocatalysts in thin-film form, functional and effective PIRET process, and facile E-F alignment, enhances the oxygen evolution with Au-CT-NR in direct sunlight and make it highly sustainable. A possible mechanism of water oxidation is proposed from the observed experimental findings.
Keywords: ceria; Electronic integration; Photocatalysis; thin film; water splitting